2006
DOI: 10.1089/jpm.2006.9.371
|View full text |Cite
|
Sign up to set email alerts
|

Manualized Communication Interventions to Enhance Palliative Care Research and Training: Rigorous, Testable Approaches

Abstract: Palliative care practice requires excellent communication between the patient, family, and clinical team. Experts in the field have proposed a variety of communication interventions that can be used in the palliative care setting. However, these interventions are at a high level of generality: the specifics of each intervention are not well codified; the individual steps in each intervention are not easily reproducible and thus not comparable between practitioners; the methods to measure adherence to these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Communication cannot become protocolized to the point of being robotic and missing the opportunity to respond to individual needs. It is possible to develop protocols or manuals for a communication intervention that allow rigorous evaluation of a standardized intervention but also allow the communication to respond to the needs of the individual 77. It is also important to allow individual clinicians to use their intuition and individual communication styles to respond in ways that are authentic.…”
Section: The Importance Of Protocols and Quality Improvement For Imprmentioning
confidence: 99%
“…Communication cannot become protocolized to the point of being robotic and missing the opportunity to respond to individual needs. It is possible to develop protocols or manuals for a communication intervention that allow rigorous evaluation of a standardized intervention but also allow the communication to respond to the needs of the individual 77. It is also important to allow individual clinicians to use their intuition and individual communication styles to respond in ways that are authentic.…”
Section: The Importance Of Protocols and Quality Improvement For Imprmentioning
confidence: 99%
“…Finally, although the multidimensionality of suffering makes it an ideal target for intervention by palliative care specialists and palliative care teams, it should not be assumed that these professionals have the requite skills to do so. Poor communication by health professionals can exacerbate patient and caregiver distress at end of life (71). In addition, there may be some role uncertainty as to which health professionals should address which dimension of suffering (72).…”
Section: Future Directionsmentioning
confidence: 99%
“…Unfortunately, in our health care system, the issues of advance care planning preferences are rarely discussed with patients or their families. Physicians may lack the time or training to initiate end of life discussions or may be uncomfortable approaching these issues, thinking that patients will be distressed and may be unwilling to accept these discussions (20)(21)(22)(23). Furthermore, research has shown that in about 25% of cases the physician's perception of the patient's preference was inaccurate (13).…”
Section: Discussionmentioning
confidence: 99%